Transaksi Mukhabarah di Perkebunan Banongan Kabupaten Situbondo Perspektif Hukum Ekonomi Syariah - Kartika Kartika (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2023)
The Banongan area is a tourist area and plantation owned by a Regional Company which provides a source of income for the local government. There are economic transactions carried out in this area. In practice, Banongan Plantation collaborates with several parties. The transaction used uses a mukhabarah agreement and this research also explains the distribution of profit sharing. In this research, qualitative research was used and the researcher's data collection process used observation, interview and documentation methods. Meanwhile, the data analysis uses perspective descriptive qualitative analysis techniques, namely data that is described in words or sentences. From the results of research and data analysis, it can be concluded as follows: 1) In the practice of mukhabarah at the Banongan Regional Company, the cultivators have fulfilled the pillars and also the requirements of the mukhabarah contract. And according to Islamic law, this is in accordance with the mukhabarah agreement. 2) In practice, the Banongan regional company and the cultivating farmers make an agreement as stated in the cooperation agreement letter which clearly explains the distribution of results that will be shared after the harvest period has been completed by calculating the net harvest income which has been reduced by the initial capital for cultivation and so on. etc.